Flexural Strength Enhancement in Sugarcane Bagasse-Polypropylene Biocomposite through Maleic Anhydride Grafted Polypropylene (MAPP) Addition - andre kurniawan yusuf; Juliana Anggono; Suwandi Sugondo (Mechanova, 2017)
Sugarcane bagasse has been investigated as reinforcement fiber for polypropylene matrix. Based on previous research, there should be advanced research to produce composite with mechanical characteristic (flexural strength) based on industrial needs. In this research, MAPP is in varied amounts, i.e. 0,5%, 1%, and 1,5%. Then, MAPP addition to composite is evaluated by measuring the flexural strength based on ASTM D790-12. These results were compared to the current products from the automotive industry which are made from black woodboard and brown woodboard.The result of  flexural strength testing of sugarcane bagasse composite without MAPP addition has average 15,31 MPa. MAPP addition increases the flexural strength up to 17,74 MPa at 0,5% MAPP concentration. An addition of MAPP more than 0,5% percent the flexural strength strength decreases. The flexural strength obtained is 50,1%-56,9% and 52,8%-59,9% lower than black woodboard and brown woodboard respectively.